Using Different Size of Montmorillonite Particles for Filtration-Adsorption of Nickel Metal in Electroplating Liquid Waste - Dyah Mustika Braniwati; Erfan Priyambodo (Indonesian Journal of Chemistry and Environment, 2021)
This study aims to know the effect of montmorillonite particle, which were granule and gravel of montmorillonite,prepared from the sintering method and its effectiveness in filtration-adsorption process of the nickel-metal in electroplating liquid waste. The granule and gravel of montmorillonite wereprepared by compaction and sintering processes at a temperature of 900oC. The characterization of granule montmorillonite shows the notoriously random micropore material, which the pore surface area was 8.393 m2/g. While the gravel montmorillonite has a pore surface area of 4,381 m2/g. The test was carried out by flowing electroplating waste with the crossflow filtration method and batch adsorption. The most effective decrease in the concentration of nickel-metal occurred in the granules of montmorillonite with a mass ratio of material through filtration and adsorptionwas 2:3. The effectiveness of filtration-adsorption process for removing nickel metal from liquid waste of electropaling was 83.51%.